EXERCISE IMPEDANCE CARDIOGRAPHY REVEALS IMPAIRED HEMODYNAMIC RESPONSE TO EXERCISE IN HYPERTENSIVES WITH DYSPNEA. (June 2018) - Kurpaska, M.; Krzesinski, P.; Gielerak, G.; B.Uzieblo-Zyczkowska,; Banak, M.; Stanczyk, A.; Piotrowicz, K.
Abstract : Objective: Patients with arterial hypertension (AH), especially women, often report exercise intolerance and dyspnea. However, subjective symptoms are frequently not reflected in standard, objective assessments. The aim of the study was to assess multiple parameters during controlled exercise in patients with AH, particularly the differences between subgroups identified based on sex and symptoms of reduced exercise tolerance. Design and method: Ninety-eight patients with AH (52 women; age 54.5 ± 8.2 years) were evaluated for dyspnea, levels of the NT-proBNP, exercise capacity (with cardiopulmonary exercise testing (CPET) and a 6-minute walk test (6MWT)), and hemodynamic parameters (by means of impedance cardiography) during exercise. Patients with AH were stratified by sex and history of dyspnea, yielding four subgroups: males without dyspnea (MnD, n = 38); males with dyspnea (MD, n = 8); females without dyspnea (FnD, n = 27); females with dyspnea (FD, n = 25). Results: In comparison with MnD, the FnD subgroup demonstrated higher NT-proBNP levels (29.5 ± 25.5 vs. 103.1 ± 71.6 pg/mL, p < 0.001); lower exercise capacity: shorter 6MWT distance (595.3 ± 91.5 vs. 522.9 ± 56.6 m, p < 0.001); lower peak oxygen uptake (VO2) (22.7 ± 5.2 vs. 17.0 ± 3.7 mL/min/kg, p < 0.001); higher peak stroke volume index (SVI) (52.4 ± 8.9 vs. 61.7 ± 11.2 mL/m2, p = 0.004); and higher SVI at the anaerobic threshold (AT) (50.1 ± 10.4 vs. 59.5 ± 12.6 mL, p = 0.011). In comparison with FnD, the FD subgroup covered a shorter distance during the 6MWT distance (522.9 ± 56.6 vs. 466.1 ± 87.2 m, p = 0.017), had a steeper VE/VCO2 slope (25.5 ± 2.4 vs. 29.0 ± 5.5, p = 0.004); lower values of peak stroke volume (SV) (117.4 ± 22.4 vs. 99.7 ± 18.1 mL, p = 0.017), peak cardiac output (CO) (17.0 ± 3.7 vs. 13.1 ± 2.9 L/min, p = 0.002) and lower change in CO (peak–rest) (10.5 ± 3.6 vs. 7.2 ± 2.7 L/min, p = 0.004). However, no other differences were identified (NT-proBNP, left ventricular diastolic dysfunction, or CPET parameters) Conclusions: Exercise impedance cardiography revealed an impaired hemodynamic response to exercise in hypertensive females with dyspnea. In patients with unexplained exercise intolerance exercise impedance cardiography may complement traditional exercise tests.